Analysis of Risk Factors Associated with Measles Incidence in Toddlers in South Halmahera Regency - Abdullah, Syarif; Anggraini, Novita Ana; Peristiowati, Yuly (Newinera Publisher, 2025)
Measles is an internal disease (VPD) caused by Morbilivirus. This disease is characterized by the appearance of fever, reddish spots, cough, runny nose, red eyes and rashes all over the body which generally occurs in children. Measles, also known as Morbili or Measles, is a disease caused by the measles virus of the Paramyxovirus group. Transmission can occur through air that has been contaminated by droplets (spit) of an infected person. This case tends to attack early childhood and elementary school age children. Once a person has had measles, he or she will have lifelong immunity to the disease The aim of this research is to determine the factors related to the incidence of measles in toddlers in South Halmahera Regency. The research design used is quantitative research using a